Pendampingan Advokat Menetukan Strategi Penyelesaian Case - Maharani, Eva Naura; Mufti Akbar, Afriansyah; Sinaga, Romauli Yohana; Shelomita L.T, Ruth; Maheswari, Jovita Lituhayu; Sumardiana, Benny; Abidah, Shofriya Qonitatin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article examines in depth the strategic role of the Legal Aid Clinic (KBH) in realizing access to justice for the poor and vulnerable groups who often experience obstacles in obtaining proper legal services. In this context, KBH not only functions as an institution providing legal aid, but also as a practical learning medium for law students through a clinical legal education approach. The research was conducted using a normative and empirical legal approach, where regulatory aspects and field practices are the main focus of the discussion. KBH is a very relevant means of community service because it provides real contributions to the community while strengthening students' competence in dealing with real legal cases. Through mentoring and supervision from lecturers, students are trained to conduct legal interviews, case analysis, preparation of legal documents, and provide direct legal consultation and counseling. In addition, this article highlights the importance of institutional support, supportive regulations, and synergy between universities, legal aid organizations, and the government so that the existence of KBH does not only function as a formality, but is able to provide a substantive impact on law enforcement that is fair. Therefore, KBH becomes a meeting point between the academic world and legal practice that bridges legal idealism and social reality in the community.